Entrepreneurship education effectiveness in higher learning institution: a study on Universiti Teknologi MARA / Hardy Loh Rahim, Hardi Emrie Rosly and Zanariah Zainal Abidin. - Rahim, Hardy Loh; Rosly, Hardi Emrie; Zainal Abidin, Zanariah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
The purpose of this paper is to examine the effectiveness of entrepreneurship education in Malaysia. Design/methodology/approach – This research uses standardised questionnaire approach which obtained 200 responses from university students of University Teknologi MARA (UiTM) using measures are adopted from Rae and Harris (2012). Findings – It is found that entrepreneurship education at UiTM is fairly effective in making students understand about entrepreneurship, developing business ideas and developing skills and knowledge. However, it is still lacking in developing students confidence to start a business. It is also found that education levels and students origin plays a part in the effectiveness of entrepreneurship education in UiTM. Research limitations/implications – Surveys that apply the self-assessment tool do not comprise a representative sample of all students in Malaysia’s institute of higher learning. However, research results can be used to give an indication on the general level of effectiveness entrepreneurship education in Malaysia particularly because UiTM is the biggest university in Malaysia and has won the most entrepreneurial university awards for three years running. Originality/value – The results of the research explores the state of entrepreneurship education in Malaysia since there are not many studies done despite its popularity.